Peningkatan pendapatan asli desa melalui pembinaan revitalisasi BUMDes dan tata kelola dana desa - Enni Savitri; Andreas Andreas; Volta Diyanto (Unri Conference Series: Community Engagement, 2019)
Village finances are strategic for both the village and the government in the district. the importance of the village finances is upheld by the provision of the bill for village number 6 of 2014. The conditions in the village actually indicate a financial pattern in the village done by village device. Starting from the planning stage must be organized with village people because in the performance and financial circumference of the village must be managed by transparent principles, accountable, passive participation also orderly and budgetary discipline. Service towards composing document planning for village development. Teaching planning on using the synopsis account to village officials includes exposure issues, budget postings and financial reports in APBDes. A buffer of BUMDes, Equal perception of village personnel, BUMDes regulation, Job Desk Managerial BUMDes. The targets are the village devices of the village treasurer. An application of coaching and wingman. The level of application for the program’s objectives was created BUMDes road map and reported financial funds in the village have used the Siskeudes system.